Rethinking The Future of Auditing: How an Integrated Continuous Auditing Approach Can Leverage the Full Potential of Continuous Auditing - Sebastian Weins; Bastian Alm; Tawei Wang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The concept of Continuous Auditing has been around for more than three decades. The ongoing discussion on the benefits and models on adoption has made Continuous Auditing become a more critical issue. Although a lot of progress has been made in previous years, we argue that the entire potential of Continuous Auditing still remains unrevealed. This paper provides a new conceptual framework on how to bring Continuous Auditing to the next level. It goes beyond the existing technical concepts and solutions for implementation by developing a more holistic Integrated Continuous Auditing Approach. We illustrate how Continuous Auditing can be adopted in order to increase audit efficiency by enabling a new collaborative design between internal and external auditors as well as by readjusting the roles of different auditing parties.
Keywords: 330; continuous auditing; internal audit; audit collaboration